Pyrethroid genetic resistance in the dengue vector (Aedes aegypti) in Posadas, Argentina - Fay, Jessica V.; Espinola, Sonia L.; Boaglio, María V.; Blariza, María J.; Lopez, Karen; Zelaya, Fabian; Kulkarni, Manisha A.; Argüelles, Carina F.; Ferreras, Julian A.; Miretti, Marcos M. (Frontiers in Public Health, 2023)
Pyrethroids are extensively used to control adult populations of the arboviral vector Aedes aegypti, rising concerns regarding the increasing frequency and distribution of insecticide resistance mutations (kdr: knock down resistance) in the voltage gate sodium channel gene (Nav). Widespread use of pyrethroids impose a threat to the success of mosquito control and to the environment. In this work we investigated the presence of two kdr mutations (V1016I and F1534C) in the Nav gene and their distribution across four neighbourhoods in Posadas, Argentina, with different Aedes abundance and contrasting socio-economic status (SES). Alleles at each locus were interrogated using TaqMan SNP genotyping assays in DNA extracted from adult females collected in a longitudinal study. We report the presence of pyrethroid both resistance alleles (kdr 1016I=29.08%, kdr 1534C=70.70%) among adult females. The combined kdr genotypes frequency reveals that approximately 70% of local adult females have an enhanced resistance to pyrethroids. The proportion of resistant adult females (with at least one kdr allele in each locus) and Aedes abundance both showed an uneven distribution between neighbourhoods with different SES (p<0.001). In high SES neighbourhoods we found more mosquitoes and higher frequency of pyrethroid resistance, possibly as a consequence of differing public health interventions, social habits and insecticide use. This is the first report of kdr mutations in Ae. Aegypti in Northeast of Argentina. Our results emphasize the need of within population (city) distribution analyses of kdr mutations and highlights the relevance of incorporating insecticide resistance monitoring within the Integrated Vector Management initiative.